Adjunctive testing by cytology, p16/Ki‐67 dual‐stained cytology or HPV16/18 E6 oncoprotein for the management of HPV16/18 screen‐positive women. Issue 9 (22nd December 2020) - Torres‐Ibarra, Leticia; Lorincz, Attila T.; Wheeler, Cosette M.; Cuzick, Jack; Hernández‐López, Rubí; Spiegelman, Donna; León‐Maldonado, Leith; Rivera‐Paredez, Berenice; Méndez‐Hernández, Pablo; Lazcano‐Ponce, Eduardo; Salmerón, Jorge
Abstract: High‐risk human papillomavirus type 16/18 (HPV16/18) genotyping is unable to accurately discriminate nonprogressive infections from those that will progress to cervical cancer. Our study aimed to assesses if additional testing either with liquid‐based cytology (LBC) or the putative progression markers p16/Ki‐67 and HPV16/18 E6 oncoprotein (E6) can improve the efficiency of HPV16/18 genotyping for triaging high‐risk HPV (hrHPV)‐positive women through better cancer risk stratification. Women attending colposcopy after positive HPV16/18 genotyping results within the Forwarding Research for Improved Detection and Access for Cervical Cancer Screening and Triage (FRIDA) hrHPV‐based screening study in Tlaxcala, Mexico, underwent further testing with LBC, p16/Ki‐67 dual‐stained (DS) cytology and E6. We calculated measures of test performance for detecting histologically confirmed cervical intraepithelial neoplasia grade 2 or higher (CIN2+) and grade 3 or higher (CIN3+). A number of 475 (64.3%) of 739 HPV16/18‐positive women had complete results for all tests. Triage positivity rates were 14.1%, 18.5% and 24.4%, for LBC, E6 and DS, respectively. Compared with LBC, DS had higher sensitivity (24.4% vs 60.0%) although lower specificity (87.0% vs 79.3%) for CIN3+ ( P < .001), whereas E6 had a sensitivity of 37.8% and a specificity of 83.5%. No invasive cancer was missed by DS or E6, but 75% were in normal cytology. DS test was associated with nearly 75% reduction of colposcopy referrals compared with the direct referral of all HPV16/18‐positive women, giving the least number of colposcopies (n = 4.3) per CIN3+ detected. We show that adjunctive testing of HPV16/18‐positive women with DS may greatly reduce unnecessary colposcopy referrals within HPV‐based screening employing HPV16/18 genotyping while retaining acceptable sensitivity for CIN2+ and CIN3+. Abstract : What's new? Testing for HPV 16/18 is currently used in many screening programs for cervical cancer. However, standard HPV genotyping cannot determine whether or not the infection is likely to progress to cancer. In this study, the authors found that when dual‐stained cytology (DS) for p16/Ki‐67 is added to the screening, it may reduce unnecessary colposcopy referrals by as much as 75%. Meanwhile, this combination testing is also sensitive enough that invasive lesions can be caught early. This approach to HPV triage may thus be significantly more efficient, while reducing unnecessary procedures.